Mucosal Immunization Against Pertussis: Lessons From the Past and Perspectives - Dubois, Violaine; Locht, Camille (Frontiers in Immunology, 2021)
Background: Current vaccination strategies against pertussis are sub-optimal. Optimal protection against Bordetella pertussis, the causative agent of pertussis, likely requires mucosal immunity. Current pertussis vaccines consist of inactivated whole B. pertussis cells or purified antigens thereof, combined with diphtheria and tetanus toxoids. Although they are highly protective against severe pertussis disease, they fail to elicit mucosal immunity. Compared to natural infection, immune responses following immunization are short-lived and fail to prevent bacterial colonization of the upper respiratory tract. To overcome these shortcomings, efforts have been made for decades, and continue to be made, toward the development of mucosal vaccines against pertussis. Objectives: In this review we systematically analyzed published literature on protection conferred by mucosal immunization against pertussis. Immune responses mounted by these vaccines are summarized. Method: The PubMed Library database was searched for published studies on mucosal pertussis vaccines. Eligibility criteria included mucosal administration and the evaluation of at least one outcome related to efficacy, immunogenicity and safety. Results: While over 349 publications were identified by the search, only 63 studies met the eligibility criteria. All eligible studies are included here. Initial attempts of mucosal whole-cell vaccine administration in humans provided promising results, but were not followed up. More recently, diverse vaccination strategies have been tested, including non-replicating and replicating vaccine candidates given by three different mucosal routes: orally, nasally or rectally. Several adjuvants and particulate formulations were tested to enhance the efficacy of non-replicating vaccines administered mucosally. Most novel vaccine candidates were only tested in animal models, mainly mice. Only one novel mucosal vaccine candidate was tested in baboons and in human trials. Conclusion: Three vaccination strategies drew our attention, as they provided protective and durable immunity in the respiratory tract, including the upper respiratory tract: acellular vaccines adjuvanted with lipopeptide LP1569 and c-di-GMP, outer membrane vesicles and the live attenuated BPZE1 vaccine. Among all experimental vaccines, BPZE1 is the only one that has advanced into clinical development.